2009
DOI: 10.1016/j.ejvs.2008.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Arterioenteric Fistulation – A Systematic Literature Analysis

Abstract: Secondary arterioenteric fistula continues to be an extremely serious complication after surgery on aorta and its branches. Every effort must be made to arrive at a rapid diagnosis. The best therapeutic option seems to be axillobifemoral revascularization and subsequent graft removal, which however, requires haemodynamically stable patients. Endovascular repair may serve as a bridge to open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
112
1
19

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 185 publications
4
112
1
19
Order By: Relevance
“…The use of silverimpregnated graft shortens the operation time and, currently, is a widely accepted technique. The perioperative mortality rate in our patients was 37.5% and was similar to the rate reported by Bergqvist et al [13] (38-47%) referring to the type of surgery we performed. In another systematic review, Aguilar et al reported even lower early mortality rate of 8-13.3% [32].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The use of silverimpregnated graft shortens the operation time and, currently, is a widely accepted technique. The perioperative mortality rate in our patients was 37.5% and was similar to the rate reported by Bergqvist et al [13] (38-47%) referring to the type of surgery we performed. In another systematic review, Aguilar et al reported even lower early mortality rate of 8-13.3% [32].…”
Section: Discussionsupporting
confidence: 75%
“…In another systematic review, Aguilar et al reported even lower early mortality rate of 8-13.3% [32]. The perioperative mortality rates for the most popular method globally (graft removal and axillobifemoral bypass) reported by the same authors were 42-51% [13] and 18.2-44% [32], respectively. Infection factors play a significant role in the pathogenesis of SAEF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations